2008
DOI: 10.1377/hlthaff.27.2.550
|View full text |Cite
|
Sign up to set email alerts
|

Improving Coverage And Access For Immigrant Latino Children: The Los Angeles Healthy Kids Program

Abstract: A large number of California counties have recently taken bold steps to extend health insurance to all poor and near-poor children through county-based Children's Health Initiatives. One initiative, the Los Angeles Healthy Kids program, extends coverage to uninsured children in families with incomes below 300 percent of the federal poverty level who are ineligible for Medi-Cal (California Medicaid) and Healthy Families (its State Children's Health Insurance Program). A four-year evaluation of Healthy Kids find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…A rigorous four‐year evaluation of LAHKP (Hill et al 2008) showed that the program reached the most vulnerable children, as 86 percent of new enrollees lived in households below the poverty level, 91 percent were noncitizens, and in 71 percent of the households Spanish was the language spoken. Despite the fact that 91 percent lived in households with at least one parent employed, only 9.9 percent of the households received employer sponsored dependent health insurance coverage.…”
Section: Resultsmentioning
confidence: 99%
“…A rigorous four‐year evaluation of LAHKP (Hill et al 2008) showed that the program reached the most vulnerable children, as 86 percent of new enrollees lived in households below the poverty level, 91 percent were noncitizens, and in 71 percent of the households Spanish was the language spoken. Despite the fact that 91 percent lived in households with at least one parent employed, only 9.9 percent of the households received employer sponsored dependent health insurance coverage.…”
Section: Resultsmentioning
confidence: 99%
“…We did not measure income because prior work had shown that income level is quite homogenous within the program, with 86 percent of all enrollees living in families with incomes <100 percent of FPL and nearly all the remaining under 200 percent. We did not assess immigration status because most (92 percent) enrollees are noncitizens (Hill et al 2008).…”
mentioning
confidence: 99%
“…Emergency department–based referrals to health insurance for undocumented and uninsured children, including Healthy Kids San Mateo, increased hospital revenue and decreased bad debt 37 . By using existing infrastructure to enroll children and modeling the program after the Children's Health Insurance Program (CHIP) known as Healthy Families, program enrollment improved 38 . The similarities to Healthy Families created parity with respect to access for mixed‐status families enrolled in both programs 33 .…”
Section: Models Of Fundingmentioning
confidence: 99%
“…The limited copays and low‐cost premiums were arranged on a sliding scale 34 and accessible for most families who reported lower health costs than when uninsured. However, families of children with special needs were more likely to be concerned about the costs of the copays and premiums 38 . Of note, as Healthy Kids enrollment prices increased, participation in the program decreased by about 20% associated with the premium increases, 39 reflecting persistent inequities in who can take full advantage of such programs.…”
Section: Models Of Fundingmentioning
confidence: 99%